Clearing the tracks of the White Pass & Yukon Railroad after a snow storm on the summit of White Pass, Alaska, March 20, 1899. - Hegg, Eric A., 1867-1948 (1899)
Caption on image: "Clearing the track after the snow storm on the summit of White Pass and Yukon Route. Mar 20 '99" Original image in Hegg Album 2, page 22. Original photograph by Eric A. Hegg 690A; copied by Webster and Stevens 46.A. Klondike Gold Rush.